Unlocking the potential of loyalty programs in reference to customer experience with digital wallets - Vidushi Vatsa; Bhawna Agarwal; Ruchika Gupta (Innovative Marketing, 2023)
The emergence of digital technology has fundamentally transformed how businesses generate value for their customers. One of the critical components of this paradigm shift in digital transformation is improving customer experience, which benefits both consumers and organizations. This study aims to evaluate customer experience and its influence on customer satisfaction and loyalty in the digital wallet domain. It also analyzes the moderating role of loyalty programs. This study was conducted in the Indian context since, alongside advancements in technology and a focus on digitalization, there has been a substantial increase in the acceptance of cashless payment options. The data from 349 respondents using the snowball sampling technique were collected through Google Forms, and SmartPLS 4.0 was used for analysis.The results showed that loyalty and satisfaction are significantly influenced in the digital wallet domain if organizations work on factors affecting customer experience. The results also proved that loyalty programs moderate the relationship between customer experience and customer satisfaction.This analysis successfully unlocked the potential of loyalty programs and established that loyalty programs do not moderate customer loyalty. However, organizations must note that poorly designed loyalty programs are just like any other sale promotion scheme, which adds up to the promotional expense without achieving the overall long-term objective of sustaining loyal consumers.